Development of Early Childhood Teachers’ Competence in Creating Digital Learning Media Using Book Creator: A Qualitative Study - Aulia, Meirantie; Ima, Ima; Dwihayati Priyatmoko, Septiani; Muqodas, Idat; Intan Lestari, Oktavia; Ayu Listiyanti, Putri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the processes and outcomes of enhancing early childhood teachers’ competencies in developing digital learning media using the Book Creator application. Employing a qualitative approach with a descriptive design, the research focuses on exploring teachers’ experiences throughout a series of technology competency development activities. Data were collected through observations, semi-structured interviews, and documentation, and were analyzed thematically to identify changes in teachers’ skills and perceptions. The findings indicate that the competency development intervention effectively improved teachers’ understanding and abilities in designing digital books that integrate text, visuals, audio, and other multimedia elements. Beyond technical skills, the study also revealed an increase in teachers’ confidence in producing more creative and relevant learning materials for young children. These results highlight the importance of strengthening technological competence through structured and continuous training as a strategic effort to enhance the quality of early childhood education.